Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3201/eid2904.221397
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Invasive Meningococcal Disease, Auckland, New Zealand (Aotearoa), 2004–2020

Abstract: In support of improving patient care, this activity has been planned and implemented by Medscape, LLC and Emerging Infectious Diseases. Medscape, LLC is jointly accredited with commendation by the Accreditation Council for Continuing Medical Education (ACCME), the Accreditation Council for Pharmacy Education (ACPE), and the American Nurses Credentialing Center (ANCC), to provide continuing education for the healthcare team.Medscape, LLC designates this Journal-based CME activity for a maximum of 1.00 AMA PRA C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The OMV vaccine was tested in several clinical trials where it showed an acceptable safety profile and a strong immune response after three doses of the vaccine. The vaccination program was staggered throughout the different regions of New Zealand, delivered to different age groups at a time between 2004 and 2006, and used for infant routine vaccination until 2008 [ 45 ]. The vaccine was estimated to be 77% effective and prevented an estimated 210 cases of MenB IMD with its attendant sequelae between July 2004 and December 2008 [ 46 ].…”
Section: Licensed Outer Membrane Vesicle (Omv)-based Vaccinesmentioning
confidence: 99%
“…The OMV vaccine was tested in several clinical trials where it showed an acceptable safety profile and a strong immune response after three doses of the vaccine. The vaccination program was staggered throughout the different regions of New Zealand, delivered to different age groups at a time between 2004 and 2006, and used for infant routine vaccination until 2008 [ 45 ]. The vaccine was estimated to be 77% effective and prevented an estimated 210 cases of MenB IMD with its attendant sequelae between July 2004 and December 2008 [ 46 ].…”
Section: Licensed Outer Membrane Vesicle (Omv)-based Vaccinesmentioning
confidence: 99%
“…New Zealand has relatively high rates of invasive meningococcal disease. It has been estimated that New Zealand has an incidence over 2-fold higher than that of other high-income countries [10,11]. Māori and Pacifika communities are disproportionately affected by the disease, along with people living in deprivation [10,12].…”
Section: List Of Figuresmentioning
confidence: 99%
“…It has been estimated that New Zealand has an incidence over 2-fold higher than that of other high-income countries [10,11]. Māori and Pacifika communities are disproportionately affected by the disease, along with people living in deprivation [10,12]. This disparity is predicted to increase further with rising poverty and socioeconomic inequity in New Zealand [10].…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation